PEMBELAJARAN BI AL-NADHOR DALAM MENGHAFAL AL-QURAN BAGI SANTRI TAHFIDH DI PONDOK PESANTREN MADRASATUL QURAN - Rosihatul Ulum; Zaenal Arifin Hasan (Universitas Hasyim Asy'ari (UNHASY) Tebuireng Jombang, 2020)
Learning is an activity process that allows teachers to teach and students can receive subject matter taught by the teacher systematically and influence each other in teaching and learning activities to achieve the desired goals in a learning environment. In this study using bi al-Nadhor learning in memorizing Al-Qur'an for the students of the Islamic Boarding School Madrasatul Qur'an Tebuireng Jombang. The process of memorizing Al-Qur'an is carried out through the process of mentoring a tahfidzz teacher. The guidance process is carried out through the bi al-nadhor activity, which is reading carefully the verses of the Al-Qur'an which will be memorized by looking at the Al-Qur'an mushaf repeatedly. This study aims to explain: bi al-Nadhor learning in Islamic boarding school Madrasatul Quran. This research is a descriptive qualitative research, which is a research that is used to examine the condition of a natural object where the researcher is the key instrument, the approach used is a phenomenological approach, which means a research that is carried out intensively in detail and in depth towards an organization, institution or certain symptoms. Data collection techniques using observation, interview and documentation techniques. The data analysis technique is inductive, which is an analysis based on the data obtained and then developed into a hypothesis. The data validity testing technique uses triangulation, namely checking data from various sources in various ways, and at various times. The results showed that the bi al-Nadhor learning process was carried out in classical and individual ways, namely students were grouped according to their study groups and given guidance in the field of fashohah six times a week with material according to their level, while the individual method meant dealing directly with each of them. badal (ustadz) which is determined by the caregiver five times a week in accordance with the specified material. The study of bi al-Nadhor in the Islamic boarding school madrasatul quran is considered to be very supportive of the success of the process of memorizing the al-quran carried out by students. This bi al-Nadhor learning clearly makes a positive contribution to the memorization achievement target that has been designed and agreed upon by the tahfdih coaches, administrators and badals (ustadz) at the madrasatul quran Islamic boarding school. By learning bi al-Nadhor, it can reduce the frequency of errors in pronunciation and letter makhorijul. The implementation of bi al-Nadhor learning in memorizing the Koran for tahfidh students at the Madrasatul Qur'an Tebuireng Islamic Boarding School is sufficient and in accordance with the desired expectation from the start, namely being able to memorize 30 juz of the Qur'an correctly and precisely in accordance with the predetermined target and time is 3-4 years.